Novel telemetry predation sensors and mechanistic models reveal the tribulations of Atlantic salmon (Salmo salar) smolts migrating through lakes - Hanssen, Erlend Mjelde (The University of Bergen, 2020)
Masteroppgave i biologi BIO399 MAMN-BIO